An assessment of the challenges faced by King Sabata Dalindyebo Local Municipality in respect of the provision of electricity services - Gqwede, Indiana Indie (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPhil)--Stellenbosch University, 2018.